Whole brain surface-based morphometry and tract-based spatial statistics in migraine with aura patients: difference between pure visual and complex auras - Abagnale, Chiara; Di Renzo, Antonio; Sebastianelli, Gabriele; Casillo, Francesco; Tinelli, Emanuele; Giuliani, Giada; Tullo, Maria Giulia; Serrao, Mariano; Parisi, Vincenzo; Fiorelli, Marco; Caramia, Francesca; Schoenen, Jean; et al. (Frontiers in Human Neuroscience, 2023)
Background: The migrainous aura has different clinical phenotypes. While the various clinical differences are well described, little is known about their neurophysiological underpinnings. To elucidate the latter, we compared white matter fiber bundles and grey matter cortical thickness between healthy controls (HC), patients with pure visual auras (MA) and patients with complex neurological auras (MA+). Methods: 3T MRI data were collected between attacks from 20 patients with MA and 15 with MA+, and compared with those from 19 HCs. We analyzed white matter fiber bundles using tract-based spatial statistics (TBSS) of diffusion tensor imaging (DTI) and cortical thickness with surface-based morphometry of structural MRI data. Results: TBSS showed no significant difference in diffusivity maps between the three subject groups. As compared to HCs, both MA and MA+ patients had significant cortical thinning in temporal, frontal, insular, post-central, primary and associative visual areas. In the MA group, the right high-level visual-information-processing areas, including lingual gyrus, and the Rolandic operculum were thicker than in HCs, while in the MA+ group they were thinner. Discussion: These findings show that migraine with aura is associated with cortical thinning in multiple cortical areas and that the clinical heterogeneity of the aura is reflected by opposite thickness changes in high-level visual-information-processing, sensorimotor and language areas.